1990
DOI: 10.1055/s-2007-1024760
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, Cortisol, and Creatine Kinase Levels in Male Distance Runners During Reduced Training

Abstract: The purpose of this study was to examine if reduced training would reestablish normal testosterone, cortisol, and creatine kinase (CK) levels in male distance runners. Ten male runners (mean +/- SE) age 32.0 +/- 2.6 yrs, body fat 9.6 +/- 1.0%, VO2max 61.8 +/- 1.1 ml/kg/min) were monitored during 4 weeks of normal training (baseline training, BT) and 3 weeks of reduced training (RT). During BT running distance averaged 81 +/- 5 km/week, 6 days/week. During RT the runners reduced weekly training volume by 70% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0
9

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 14 publications
7
24
0
9
Order By: Relevance
“…We further speculated that the additional increases in serum CK activity at ALT 2 (7 days after arriving at altitude), ALT 3 (18 days after arriving at altitude) and ALT 4 (24±36 h prior to the end of the 5-week altitude camp) were due to the combined eect of hypobaric hypoxia and training, given that training intensity and/or volume increased progressively throughout the 5-week altitude training camp (Table 3). Serum CK values from ALT 2 through ALT 4 were similar to those reported in studies conducted at sea level involving well-trained male distance runners engaged in habitual endurance training, which consisted of running 81 km per week, 6 days per week (Houmard et al 1990). Despite the fact that serum CK activity was signi®cantly elevated throughout the duration of the 5-week altitude training period, our subjects were able to train very eectively and did not display any signs of being overworked, overtrained or injured.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We further speculated that the additional increases in serum CK activity at ALT 2 (7 days after arriving at altitude), ALT 3 (18 days after arriving at altitude) and ALT 4 (24±36 h prior to the end of the 5-week altitude camp) were due to the combined eect of hypobaric hypoxia and training, given that training intensity and/or volume increased progressively throughout the 5-week altitude training camp (Table 3). Serum CK values from ALT 2 through ALT 4 were similar to those reported in studies conducted at sea level involving well-trained male distance runners engaged in habitual endurance training, which consisted of running 81 km per week, 6 days per week (Houmard et al 1990). Despite the fact that serum CK activity was signi®cantly elevated throughout the duration of the 5-week altitude training period, our subjects were able to train very eectively and did not display any signs of being overworked, overtrained or injured.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, Stray-Gundersen et al (1986) observed a signi®-cant increase in serum CK activity [282 (25) U á l A1 ] in the runners following 2 weeks of increased training (additional hard interval sessions), and a decrease in serum CK activity [165 (16) U á l A1 ] after resumption of normal training. Similar ®ndings were reported by Houmard et al (1990) who observed elevated serum CK activity [168 (15) U á l A1 ] in trained male distance runners during 4 weeks of increased training (81 km per week, 6 days per week), and a decrease in serum CK activity [99 (9) U á l A1 ] during 3 weeks of reduced training (24 km per week, 6 days per week). Apple and McGue (1983) reported that serum CK activity was 12 times higher than clinically normal values in runners who regularly trained 80±160 km per week, while Dressendorfer and Wade (1983) observed elevated serum CK activity (400±500 U á l A1 ) in endurance athletes running approximately 28 km per day for 20 days in the 500-km Great Hawaiian Footrace.…”
Section: Introductionsupporting
confidence: 71%
“…Therefore, serum CK activity has been theoretically expected to be useful as a marker in exercise physiology and sports medicine for the detection of muscle injury and overwork [13]. However, previous studies on CK release have not clearly demonstrated its value as a marker for these states [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, while some studies have reported no acute changes in cortisol secretion in response to resistance exercise (Dohi et Creatine kinase (CK) is found predominantly in muscle and is released into circulation during muscular lesions. Therefore, serum CK activity has been theoretically expected to be useful as a marker in exercise physiology and sports medicine for the detection of muscle injury and overwork (Houmard et al 1990). However, previous studies on CK release have not clearly demonstrated its value as a marker for these states (Newham et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally recognized that IgA, due to its dominance in the immune system of mucous membranes, is the first line of defense against harmful environmental factors. The secretion and composition of saliva depends on the activity of the sympathetic and parasympathetic nervous systems (Houmard et al, 1990). Physical activity, stimulating the autonomous nervous system, may reduce the amount of saliva and/or inhibit its secretion.…”
Section: Introductionmentioning
confidence: 99%